Usefulness of non-native invasive tree species wood residues for pellet production - Gornik Bučar, Dominika (Les (Ljubljana), 2021)
We produced pellets from five invasive non-native tree species growing in Slovenia on a laboratory pelleting device, namely: wild chestnut (Aesculus hippocastanum), boxelder maple (Acer negundo), black locust (Robinia pseudoacacia), thorny locust (Gleditsia triacanthos) and tree of heaven (Ailanthus altissima), as well as mixtures of the raw material from the above non-native invasive species and spruce (Picea abies) in the ratios 70:30 and 50:50. Under the same production conditions, we produced a total of 15 different types of pellets. The most important physical and mechanical properties (water content, bulk density, mechanical stability and ash content) were determined for the pellets produced. The results were compared with the limits defined in the international standard SIST EN ISO 17225-2:2014. The water content and bulk density of all produced pellet types met the requirements of the standard for the highest quality class A1. The mechanical durability of the pellets produced did not meet the requirements of the standard and did not exceed 96.5% (which is the limit value for quality class B). The results suggest that black locust, thorny locust and tree of heaven have the highest potential for further optimization of the pelleting process.
Keywords: high-energy multiple impact; kakovost peletov; lesni ostanki; peletiranje; resistance to impact milling; static bending; thermal modification; trdna biogoriva; tujerodne invazivne drevesne vrste; wood